Mechanisms of co-existence of Heterocope saliens (Crustacea, Copepoda) and planktivorous fish - Ragnvald Andersen; Jens Petter Nilssen (Fauna Norvegica, 1984)
The simultaneous occurrence of Heterocope saliens and a large stock of Arctic char was investigated in the oligotrophic, coastal Lake Selura in SW Norway. Habitat-overlap of H. saliens and Arctic char was restricted mainly to June. With increasing temperature, Arctic char disappeared from the littoral and the upper water masses and inhabited the hypolimnion of the lake. The interaction between H. saliens and its important predator was minimized and thus a large population of H. saliens could be established, primarily in the littoral, but to a minor extent also in the pelagial of the lake. H. saliens can avoid elimination from lakes with strong pelagic fish predation by staying in the littoral, while both strong littoral and limnetic fish predation probably lead to elimination of H. saliens. When fish disappear during acidification, H. saliens seems to expand its area considerably and to become a permanent inhabitant of the pelagic zone. The relationship between fish predation and distribution of the other Norwegian Heterocope species is briefly discussed.